Attenuated T Cell Responses Are Associated With the Blockade of Cerebral Malaria Development by YOP1-Deficient Plasmodium berghei ANKA - Hai, Lei; Shi, Xiaoyu; Wang, Qian (Frontiers in Immunology, 2021)
Reticulon and the REEP family of proteins stabilize the high curvature of endoplasmic reticulum tubules. The REEP5 homolog in Plasmodium, Plasmodium berghei YOP1 (PbYOP1), plays an important role in the erythrocytic cycle of the P. berghei ANKA and the pathogenesis of experimental cerebral malaria (ECM), but the mechanisms are largely unknown. Here, we show that protection from ECM in Pbyop1Δ-infected mice is associated with reduced intracerebral Th1 accumulation, decreased expression of pro-inflammatory cytokines and chemokines, and attenuated pathologies in the brainstem, though the total number of CD4+ and CD8+ T cells sequestered in the brain are not reduced. Expression of adhesive molecules on brain endothelial cells, including ICAM-1, VCAM-1, and CD36, are decreased, particularly in the brainstem, where fatal pathology is always induced during ECM. Subsequently, CD8+ T cell-mediated cell apoptosis in the brain is compromised. These findings suggest that Pbyop1Δ parasites can be a useful tool for mechanistic investigation of cerebral malaria pathogenesis.